2019
DOI: 10.1021/acssuschemeng.9b00619
|View full text |Cite
|
Sign up to set email alerts
|

Primary Benzylamines by Efficient N-Alkylation of Benzyl Alcohols Using Commercial Ni Catalysts and Easy-to-Handle Ammonia Sources

Abstract: Primary benzylamines are highly important building blocks in the pharmaceutical and polymer industry. An attractive catalytic approach to access these compounds is the direct coupling of benzyl alcohols with ammonia via the borrowing hydrogen methodology. However, this approach is usually hampered by a series of side-reactions, one of the most prominent being the overalkylation of the formed primary amine. Herein, we describe a robust catalytic methodology, which utilizes commercially available heterogeneous N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 36 publications
(75 reference statements)
7
48
0
Order By: Relevance
“…Amines are widely present in natural products, pharmaceuticals, and agrochemicals. Because of their importance, many synthetic strategies such as reductive amination, , alcohol amination, and transamination, , and hydroamination , have been developed for the construction of complex amine architectures. One favored way to obtain amines is to deoxygenatively transform amides, which are prevalent in nature and synthetically accessible, into amines .…”
Section: Introductionmentioning
confidence: 99%
“…Amines are widely present in natural products, pharmaceuticals, and agrochemicals. Because of their importance, many synthetic strategies such as reductive amination, , alcohol amination, and transamination, , and hydroamination , have been developed for the construction of complex amine architectures. One favored way to obtain amines is to deoxygenatively transform amides, which are prevalent in nature and synthetically accessible, into amines .…”
Section: Introductionmentioning
confidence: 99%
“…Due to a lack of diastereoselectivity, a mixture of the two amino‐alcohols was obtained . More recently, Barta et al also reported the mono‐amination of isosorbide using a supported‐Ni catalyst and aqueous ammonia within 32 to 51 % GC yield but without information concerning the stereochemistry . We thus developed the first synthesis of this pure chiral amino‐alcohol 7 in 54 % over 2 steps from isosorbide with an excellent optical purity (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Water‐soluble iridium complex catalysts bearing N‐heterocyclic carbene ligands that enable the selective N‐monoalkylation of aqueous ammonia with a variety of alcohols were developed [26] . Meanwhile, heterogeneous catalysts using Ir, [28] Ni, [29–34] Ru, [35–37] Au−Pd, [38] and Rh‐In [39] have newly emerged. Nevertheless, there are still some restrictions in the catalytic reactions such as indispensability of organic solvent, high‐pressure atmosphere of hydrogen or ammonia, and high temperature.…”
Section: Entry Catalysts[b] Yield [%][C]mentioning
confidence: 99%